J.K. ROWLING’S HARRY POTTER AND THE DEATHY HALLOWS: THE ANALYSIS OF IMPLICIT MEANINGS - Diana, Eli; Fransisca, Shirly (JURNAL LITERARY CRITICISM, 2014)
The objects of the analyses are sentences containing implicit meanings in the novel previously mentioned. The sentences with implicit meanings are taken as data, and analyzed using descriptive and qualitative methods. The novels Harry Potter and the Deathly Hallows( 2007 ) is written by J. K. Rowling and translated into Indonesian by Listiana Srisanti entitled Harry Potter Dan Rilikui Kematian. The purpose of this research is to study the translation of implicit meanings from the source language into the target language. The results of this research show that an implicit meaning should be explicitly translated if the system of the target  language requires it, on the other hand, an implicit meaning can be explicitly translated if the system of the target language allows it, and the last, an implicit meaning should be explicitly translated if the meaning causes ambiguity or vagueness in the target language. Keywords: Implicit Meaning, Implicit Referential Meaning, Implicit Organizational Meaning and Implicit Situational Meaning